The Augment In Haya And Ekegusii - Choti, Jonathan (My University, 2022)
This article examines the behavior of the augment in Haya (E22) and Ekegusii (E42), two Bantu Zone E languages, revealing many similarities and a few differences between the Haya and Ekegusii augment. In both languages, morphosyntactic, semantic, and pragmatic requirements regulate the behavior of the augment. The common shape of the augment is a vowel (V, namely /a/, /e/, and /o/. Besides, Ekegusii has the CV shape in ri- and chi- of class 5 and 10, respectively. Augmented nouns in both languages are the default but are ambiguous between a specific and non-specific reading. In Haya and Ekegusii, the augment is not marked on proper names, most kinship terms, and vocative nouns because these pick out specific referents. Nouns used as adverbs of location, time, and manner omit the augment in both languages. The two languages require the augment in predicative and associative constructions. In complex nouns, both elements require the augment but in compound nouns, only the first is augmented in both languages. The two languages allow the augment in gerunds but not in infinitives. Most pronominals require the augment in the two languages. Haya and Ekegusii disallow the augment in interrogative and negative constructions, proverbs, and nouns modified by 'any' to signal non-specific reference. In both languages, affirmative declaratives require the augment. Emphatic nouns in topic and contrastive focus positions require the augment to mark emphasis and specificity even in negative contexts. These features of the augment in Haya and Ekegusii confirm that the so-called augment is actually a bound article.
Keywords: HUMANITIES and RELIGION::Languages and linguistics::Other languages::Bantu languages; Augement; Haya and Ekegusii